2020
DOI: 10.1111/jan.14575
|View full text |Cite
|
Sign up to set email alerts
|

Acceptance and commitment therapy for chronic pain conditions on functioning: A systematic review protocol

Abstract: Aim To explore the efficacy of acceptance and commitment therapy (ACT) on chronic pain in terms of functioning; and to identify the most promising modes and patterns for implementing ACT. Design Systematic review and meta‐analysis. Methods We will include randomized controlled trials which focus on the efficacy of ACT on chronic pain conditions with functioning as the primary outcome. Seven databases have been searched and grey literature will also be systematically searched for. Eligible studies will be scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…In other words, all the aspects of their life will be influenced by pain regardless of the other personality traits. In this situation, psychological interventions such as Acceptance and Commitment Therapy help people make difference between their whole selves and their pain and do not consider the pain as their total existence (39,41).…”
Section: Discussionmentioning
confidence: 99%
“…In other words, all the aspects of their life will be influenced by pain regardless of the other personality traits. In this situation, psychological interventions such as Acceptance and Commitment Therapy help people make difference between their whole selves and their pain and do not consider the pain as their total existence (39,41).…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, a random‐effects model was adopted to pool data, and subgroup analysis was performed to determine potential sources of heterogeneity. Based on relevant reviews (Du et al, 2021a; Li, Wu, et al, 2021) and characteristics of the included studies, we tabulated possible factors for subgrouping, such as different cultural contexts and intervention delivery formats. Sensitivity analysis was performed by removing studies unavailable in English to check whether the pooled results still hold.…”
Section: The Reviewmentioning
confidence: 99%
“…Non-pharmacological interventions have been recommended for symptom management in people with advanced cancer (Malakian et al, 2022). Acceptance and Commitment Therapy, a novel form of Cognitive Behavioural Therapy (CBT), has gained popularity worldwide in healthcare research and practice (Du et al, 2021a).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous evidence from systematic reviews have reported the positive effects of the ACT for depression, anxiety and subjective well-being through improving psychological flexibility among clinical and non-clinical people (Gloster et al, 2020;Stenhoff et al, 2020). Compared with alternative methods, the ACT had supporting findings on the effectiveness on patients' problems, such as depression, anxiety, chronic pain and cancer adaptation (Du et al, 2021;Mathew et al, 2021;Twohig & Levin, 2017). Meanwhile, the ACT showed positive effects in healthcare professionals working with dementia by reducing anxiety and burnout (Montaner et al, 2021) and could reduce perceived stress and improve psychological flexibility of nurses working in psychiatric wards (Zarvijani et al, 2021).…”
Section: Introductionmentioning
confidence: 99%